EFFORTS TO INCREASE BREAST MILK PRODUCTION: LITERATURE REVIEW - Rahimah, Hayatul; fadhilah, Rohmatul (jfpublisher, 2022)
Introduction.Breast milk is the ideal nutrition for babies and the most perfect main food for babies. Breast milk has a composition of nutrients that are in accordance with the baby's needs to grow and develop optimally. However, Problems of mothers in breastfeeding are still often found due to various factors, one of which is not smooth milk production. The purpose of this study was to find out what efforts can be made to increase breast milk production. Method.This study used the literature review. Results&Analysis.Efforts to increase breast milk production were: sources of natural ingredients, massage, giving positive affirmations. Discussion.Breast milk production is strongly influenced by physiological and psychological factors, so it is necessary to combine various efforts.